Promotion of coffee-based agroforestry and women’s livelihoods in Vietnam - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
In northwest Vietnam, women's unions in nine provinces and ten local NGOs used "Training for Trainers” materials developed by CCAFS partners in the World Agroforestry Center (ICRAF) and CARE International to empower women and strengthen 65 Village Savings and Loan Associations in the production and marketing of coffee. More than 10,000 farmers have been trained to date, with a potential impact of ~1 Mt carbon sequestration on 20,000 ha and 350,000 indirect beneficiaries, 50% of which are ethnic minority women.